Reduced specificity in episodic future thinking in posttraumatic stress disorder - Kleim, B; Graham, B; Fihosy, S; Ehlers, A; al., E (SAGE Publications, 2014)
Posttraumatic stress disorder (PTSD), one of the most common disorders following trauma, has been associated with a tendency to remember past personal memories in a nonspecific, overgeneral way. The present study investigated whether such a bias also applies to projections of future personal events. Trauma survivors (N = 50) generated brief descriptions of imagined future experiences in response to positive and negative cues in a future-based Autobiographical Memory Test. Survivors with PTSD imagined fewer specific future events in response to positive, but not to negative, cues, compared to those without PTSD. This effect was independent of comorbid major depression. Reduced memory specificity in response to positive cues was related to appraisals of foreshortened future and permanent change. Training to enhance specificity of future projections may be helpful in PTSD and protect against potentially toxic effects of autobiographical memory overgenerality.